Selected topics in biomedical circuits and systems - Je, Minkyu; Sunwoo, Myung Hoon (River Publishers, 2021)
This book, which belongs to the "Tutorials inCircuits and Systems" series, provides readers with an overview of new developments in the field of biomedical circuits and systems. It covers basic information about system-level and circuit-level requirements, operationprinciples, key factors of considerations, and design/implementation techniques, as well as recent advances in integrated circuits and microsystems for emerging biomedical applications.
Keywords: Biomedical engineering.; Medical electronics.; Integrated circuits.; elektronické knihy; electronic books